Cavefish eye loss in response to an early block in retinal differentiation progression - Stemmer, Manuel; Schuhmacher, Laura-Nadine; Foulkes, Nicholas S.; Bertolucci, Cristiano; Wittbrodt, Joachim (Development, 2015)
Skip to Next Section: The troglomorphic phenotype shared by diverse cave-dwelling animals is regarded as a classical example of convergent evolution. One unresolved question is whether the characteristic eye loss in diverse cave species is based on interference with the same genetic program. Phreatichthys andruzzii, a Somalian cavefish, has evolved under constant conditions in complete darkness and shows severe troglomorphic characteristics, such as complete loss of eyes, pigments and scales. During early embryonic development, a complete eye is formed but is subsequently lost. In Astyanax mexicanus, another blind cavefish, eye loss has been attributed to interference during eye field patterning. To address whether similar pathways have been targeted by evolution independently, we investigated the retinal development of P. andruzzii, studying the expression of marker genes involved in eye patterning, morphogenesis, differentiation and maintenance. In contrast to Astyanax, patterning of the eye field and evagination of the optic vesicles proceeds without obvious deviation. However, the subsequent differentiation of retinal cell types is arrested during generation of the first-born cell type, retinal ganglion cells, which also fail to project correctly to the optic tectum. Eye degeneration in both species is driven by progressive apoptosis. However, it is retinal apoptosis in Phreatichthys that progresses in a wave-like manner and eliminates progenitor cells that fail to differentiate, in contrast to Astyanax, where lens apoptosis appears to serve as a driving force. Thus, evolution has targeted late retinal differentiation events, indicating that there are several ways to discontinue the development and maintenance of an eye.